Plant Food Processing Tools at Early Neolithic Göbekli Tepe - Dietrich, Laura (Archaeopress Publishing, 2021)
Plant Food Processing Tools at Early Neolithic Göbekli Tepe reconstructs plant food processing at this key Pre-Pottery Neolithic (9600-8000 BC) site, with an emphasis on cereals, legumes and herbs as food sources, on grinding and pounding tools for their processing, and on the vessels implied in the consumption of meals and beverages. Functional investigations on grinding and pounding tools and on stone containers through use-wear and residue analyses are at the core of the book. Their corpus amounts to more than 7000 objects, constituting thus the largest collection published so far from the Neolithic of Upper Mesopotamia. The spectrum of tools and of processed plants is very broad, but porridges made of cereals, legumes and herbs, and beers predominate over bread-like food. The find contexts show that cooking took place around the well-known monumental buildings, while the large quantity of tools suggests feasting in addition to daily meals.